2018
DOI: 10.1186/s12885-018-4776-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the MRE11-RAD50-NBS1 (MRN) complex in rectal cancer correlates with poor response to neoadjuvant radiotherapy and prognosis

Abstract: BackgroundThe MRE11/RAD50/NBS1 (MRN) complex plays an essential role in detecting and repairing double-stranded breaks, and thus the potential roles of MRE11, RAD50 and NBS1 proteins in the pathogenesis of various cancers is the subject of investigation. This study was aimed at assessing the three-protein panel of MRN complex subunits as a potential radiosensitivity marker and evaluating the prognostic and clinicopathological implications of MRN expression in rectal cancer.MethodsSamples from 265 rectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 43 publications
7
50
0
Order By: Relevance
“…This is a similar result to our finding that low postoperative RAD50 expression was associated with worse DFS and OS in early tumour stage and low-grade rectal cancer [58]. However, we found that with RAD50, in combination with other proteins, the MRN complex (MRE11/RAD50/NBS1) behaves quite differently from RAD50 alone [59]. Rectal cancer with a high expression of MRN complex proteins was associated with worse DFS and OS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is a similar result to our finding that low postoperative RAD50 expression was associated with worse DFS and OS in early tumour stage and low-grade rectal cancer [58]. However, we found that with RAD50, in combination with other proteins, the MRN complex (MRE11/RAD50/NBS1) behaves quite differently from RAD50 alone [59]. Rectal cancer with a high expression of MRN complex proteins was associated with worse DFS and OS.…”
Section: Discussionsupporting
confidence: 90%
“…Immunohistochemical staining preparation was performed as described previously [59]. Prepared slides were incubated with a monoclonal anti-RAD52 primary antibody, clone 5H9 (1:500 dilutions, Life Span Bioscience #LS-B1709; Seattle, WA, USA) for 60 min at room temperature.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…This complex, in combination with ataxia telangiectasia mutated (ATM), coordinates the cellular detection and repair of DNA double-strand breaks (DSBs) (Altan et al, 2016). High expression of MRE11-RAD50-NBS1 is associated with poor prognosis and chemoresistance in GC (Altan et al, 2016) as well as poor response to neoadjuvant radiotherapy and prognosis in rectal cancer (Ho et al, 2018). The MRN complex is frequently not detected in low-grade epithelial ovarian cancer, suggesting high sensitivity to the PARP inhibitor (Brandt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] Lee et al recently reported obesity as an independent negative predictive factor for complete response to CCRT in rectal cancer. 35,36 As we known, tumor response could reflects early response to treatments and related to late response outcomes including recurrence and survival. Many studies also indicate that obesity is a common risk factor for cardiovascular disease and is an indicator of poor prognosis in multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%